TLR2 and Dectin-1 Signaling in Mouse Hematopoietic Stem and Progenitor Cells Impacts the Ability of the Antigen Presenting Cells They Produce to Activate CD4 T Cells - Alba Martínez; Cristina Bono; Daniel Gozalbo; Helen S. Goodridge; M. Luisa Gil; Alberto Yáñez (Cells, 2020)
Microbial recognition by pattern recognition receptors (PRRs) expressed on hematopoietic stem and progenitor cells (HSPCs) not only activates myelopoiesis but also programs the function of the monocytes and macrophages they produce. For instance, changes in HSPC programming modify the ability of macrophages derived from them to produce inflammatory cytokines. While HSPCs exposed to a TLR2 agonist give rise to tolerized macrophages (lower proinflammatory cytokine production), HSPCs treated with Dectin-1 ligands produce trained macrophages (higher proinflammatory cytokine production). However, nothing is known about the impact of HSPC exposure to microbes on the function of antigen presenting cells (APCs). In this study we evaluated whether treatment of murine bone marrow HSPCs with a TLR2 or Dectin-1 ligand impacts the antigen presenting capacity of APCs derived from them in vitro. Following activation with microbial ligands or Candida albicans yeasts, APCs derived from TLR2/Dectin-1-programed HSPCs exhibit altered expression of MHCII (signal 1), co-stimulatory molecules (CD40, CD80 and CD86; signal 2) and cytokines (TNF-α, IL-6, IL-12 p40 and IL-2; signal 3). Moreover, APCs derived from TLR2/Dectin-1-programed HSPCs prime enhanced Th1 and Th17 responses, which are important for antifungal defense, in CD4 T cell cocultures. Overall, these results demonstrate for the first time that microbial detection by bone marrow HSPCs can modulate the adaptive immune response by inducing the production of APCs with an altered phenotype.